ACCOUNTING IN THE CONTEXT OF DIGITALIZATION - Kupenova, Zhulduz K; Baimukhanova, Sariya Baimukhanovna (Journal of Critical Realism in Socio-Economics (JOCRISE), 2024)
There is mounting evidence that the deployment of digital technologies by organizations not only affects the economics of operational and managerial processes but also mobilizes extensive social and organizational effects. Digitization impacts the form, substance, and provenance of internal accounting information with attendant consequences on the behavior and actions of organizational participants and on the functioning of enterprises more widely. Knowledge about the influence of the deployment of digital technologies on management accounting thinking, processes, and practices is starting to take shape. This article explores some of the issues that are coming to light. The purpose of the study of digital accounting is: to study business modeling, to imagine what it should become for the company to thrive in the market. Solving these problems will give you an understanding of how the digital accounting business makes decisions to survive in the market. In connection with the process of digitization, the economic entities of companies are integrated through mergers and acquisitions. The digitalization of the accounting business requires the existence and renewal of various types of sustainability, which include: economic sustainability, which can be achieved through the creation of development strategies and digital tools. This paper reviews the accounting literature that focuses on four Internet-related technologies that have the potential to dramatically change and disrupt the playing field for accountants and accounting researchers in the near future. These include cloud, big data, blockchain, and artificial intelligence (AI). For instance, access to distributed ledgers (blockchain) and big data supported by cloud-based analytics tools and AI will automate decision making to a large extent. These technologies may significantly improve financial visibility and allow more timely intervention due to the perpetual nature of accounting. However, given the number of tasks of which technology has relieved accountants, these technologies may also lead to concerns about the profession`s legitimacy and the role of accountants. The findings suggest that scholars have not given sufficient attention to these technologies and how these technologies affect the everyday work of accountants. Research is urgently needed to understand the new kinds of accounting required to manage firms in the changing digital economy and to determine the new skills and competencies accountants may need to master to remain relevant and add value. The paper outlines a set of questions to guide future research